Pengaruh Brand Image, Service Quality, dan Customer Relationship Management Terhadap Customer Loyalty - Hendy, Samuel; Keni, Keni (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This research is being shown in order to learn how brand image, service quality and customer relationship management can affect customer loyalty one of these coffee shops in Jakarta. This research can be classified as quantitative and descriptive research which consist of primary data that being gather by online questionnaire, in other word survey. These coffee shops customer that located in Jakarta are the sample in this research. The data that has been gathered are being collected from 150 customers. As the result, this research shown from these coffee shops customer in Jakarta are 1) Brand image affect the customer loyalty in positive way. 2) Service quality give positive impact toward customer loyalty. 3) There are positive clout that customer relationship management give toward customer loyalty